DEVELOPMENT OF PRIMARY SCHOOL STUDENTS' MATHEMATICAL THINKING THROUGH MODERN PEDAGOGICAL TECHNOLOGIES - Hasanova Umida, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This article analyzes the theoretical and empirical foundations of using modern pedagogical technologies in the process of developing mathematical thinking among primary school students. Recent research and international experiences regarding the effectiveness of problem-based learning, information and communication technologies, game methods, and creative approaches are carefully examined.